1998
DOI: 10.1016/s0012-821x(98)00124-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of widespread Cretaceous remagnetisation in the Iberian Range and its relation with the rotation of Iberia

Abstract: A palaeomagnetic investigation has been carried out at 13 sites of Jurassic age in the Iberian Range (northern Spain). Two components of remanent magnetisation have been found at each site. A primary high-temperature component shows an average counterclockwise rotation with respect to the north of 33 š 2º clockwise about a vertical axis corresponding to the absolute rotation of the Iberian plate since the Jurassic. A secondary low-temperature component shows a systematic declination difference of 16 š 4º with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 39 publications
(65 reference statements)
3
30
0
Order By: Relevance
“…Previous paleomagnetic studies in Permian (subvolcanic) and Mesozoic (limestones) rocks in the region have reported primary Permian and Oxfordian components (Calvin et al, 2014 andJuárez et al, 1994 respectively) as well as Lower Cretaceous remagnetizations (Juárez et al, 1998;Gong et al, 2008). However, reported declinations of all these results should be used with caution since recent data from younger Triassic to Eocene units confirmed the occurrence of clockwise rotations (CW) related to Alpine compression (Mauritsch et al, 2018).…”
Section: Geological Settingmentioning
confidence: 96%
“…Previous paleomagnetic studies in Permian (subvolcanic) and Mesozoic (limestones) rocks in the region have reported primary Permian and Oxfordian components (Calvin et al, 2014 andJuárez et al, 1994 respectively) as well as Lower Cretaceous remagnetizations (Juárez et al, 1998;Gong et al, 2008). However, reported declinations of all these results should be used with caution since recent data from younger Triassic to Eocene units confirmed the occurrence of clockwise rotations (CW) related to Alpine compression (Mauritsch et al, 2018).…”
Section: Geological Settingmentioning
confidence: 96%
“…Mean locality directions for component A, calculated after these percentages of full bedding correction, are also given in Table 3. Component B is considered to be the primary Jurassic component, based on: 1) the presence of normal and reversed polarities of magnetisation which is consistent with the pattern of reversals of the Earth's magnetic field for the Jurassic period (GRADSTEIN et al, 1994); 2) the stratigraphic consistency of polarity of the magnetisation; 3) fold test results that indicate a pre-folding acquisition of the magnetisation and 4) the inclination values obtained after bedding correction that are in agreement with the expected Jurassic inclinations (SCHOTT et al, 1981;STEINER et al, 1985;GALBRUN et al, 1990;JUA´REZ et al, 1996, 1998and GIALANELLA, 1999. The inclination variability of component B is related with the Jurassic path of the Iberian APWp, which is in agreement with the Jurassic segment of the North-American APWp proposed by VAN FOSSEN and KENT (1990).…”
Section: Palaeomagnetic Resultsmentioning
confidence: 63%
“…To explain remagnetisations affecting extensive areas, which were tectonically active during the times of remagnetisation, the formation of authigenic magnetite associated with tectonically driven fluid migration has been proposed (MCCABE et al, 1983;OLIVER, 1986;SUK et al, 1990SUK et al, , 1993. A thermoviscous mechanism related with heating has also been suggested (e.g., DOBSON and HELLER, 1992;VILLALAI´N, 1995;JUA´REZ et al, 1998).…”
Section: Remagnetisationmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that remagnetization of the pre-Aptian rocks happened around this time, probably connected to a thermal event due to extensional tectonics. Such mechanism has been already invoked to explain remagnetization of Mesozoic carbonates in Iberia (e.g., Juárez et al, 1996Juárez et al, , 1998Dinarès-Turell and García-Senz, 2000). There is an other disconformity level, which could be candidate for the time of remagnetization, a post-Cenomanian one.…”
Section: Discussionmentioning
confidence: 95%